Conteptual Metaphor in Manchester United Chants: A Semantics Study - Indriyono, Fajar; Simatupang, Ervina CM (Universitas Galuh, 2025)
This research examines the use of conceptual metaphors in Manchester United football chants through a cognitive linguistics lens, analyzing how metaphorical language constructs fan identity and collective emotion. Understanding metaphor in sports discourse is crucial for comprehending the psychological and social dimensions of fandom. The study aims to identify the types and cognitive functions of conceptual metaphors in the club’s chants. Using qualitative metaphor analysis, the research analyzes 32 chants from match recordings, fan forums, and official archives (2010–2023), applying Lakoff and Johnson’s (1980) framework of conceptual metaphor theory. Data is categorized into structural, ontological, and orientational metaphors, with additional analysis of their frequency and contextual usage. Findings reveal a predominance of war metaphors , reflecting the conceptualization of football as conflict, alongside kinship and journey metaphors , which reinforce group identity and shared purpose. The study concludes that these metaphorical systems shape fan cognition, emotional engagement, and cultural memory. This analysis enhances our understanding of how language functions in sports communities, offering insights into the cognitive underpinnings of fan behavior and the role of metaphor in constructing collective identity.